Separation of Lipopolvsaccharides and Heparin Sodium by Activated Charcoal Adsorption and Ultrafiltration Process - Li, C.Y.; Nai, Y.F.; Qian, X.; Li, H.Y.; Peng, G.P. (Asian Journal of Chemistry, 2015)
In this study, a harmful lipopolvsaccharides (endotoxin) was separated by membrane and activated charcoal from another polysaccharide with 12 kDa molecular weight, heparin sodium, which was widely used as an injectable anticoagulant. The concentration of endotoxin was investigated by dynamic turbidity method. Meanwhile, removal efficiency of endotoxin from heparin was 80.9, 5.8 and 98.8 % with 1.0 % (w/w) activated charcoal, 200 kDa polyether sulfone membrane and 200 kDa hybrid membrane, respectively. The loss of heparin was 15.7, 4.8 and 4.1 % correspondingly. Due to the similar polysaccharide of heparin and endotoxin, activated charcoal absorption may be limited by saturating and competitive adsorption. Compared with the endotoxin rejection and heparin retention, hybrid ultrafiltration membrane showed many advantages and also provided theoretical support for industrial manufacturing of heparin injection for removing endotoxin.